Research on parallel AES encryption algorithm based on a ternary optical computer - Song, Kai; Liu, Shuzhe; Wang, Hejie; Yang, Sheng; Yan, Liping; Zhang, Sulan (Optics communications, 2025)
The Advanced Encryption Standard (AES) encryption algorithm has never been broken since its introduction, and its security has been widely recognized and adopted widely by numerous countries and organizations. However, the algorithm requires dozens of iterations and each iteration involves a large number of computations, so there are problems such as low encryption efficiency and high computational costs. Aiming at these problems, this paper combines the characteristics of ternary optical computer (TOC), such as many data bits, parallel computation, three-valued encoding, to study and propose a parallel AES encryption scheme based on TOC. This scheme leverages the parallel advantages of TOC to improve the block-by-block encryption mode in the AES encryption algorithm. By employing a parallel computing strategy, it effectively reduces the execution time of the algorithm and significantly enhances encryption efficiency. In addition, this paper introduces three-valued operation logic on the basis of binary Exclusive OR(XOR) operation and constructs a set of three-valued XOR (T-XOR) standards to further improve the operation efficiency of AES encryption algorithm on TOC. Through the in-depth analysis of the algorithm resource consumption and time efficiency, and combined with the experimental verification, it can be concluded that the parallel AES encryption algorithm based on TOC has better computing efficiency and time effectiveness, which demonstrates the advantages of TOC in dealing with large-scale computing tasks.